'Is hearing believing?': A study of voices and beliefs in psychosis and trauma. (August 2022) - Rajanthiran, Leon; Curtis, Guy; Ayalde, Jeremiah; Orr, Kenneth; Melvill-Smith, Peter; Banerjee, Amit; Schenk, Meta; Wearne, Deborah
Objective: This study compared voice characteristics and beliefs in participants diagnosed with post-traumatic stress disorder (PTSD) with dissociation, schizophrenia (SCZ) and both diagnoses of SCZ and PTSD. The relationship between dissociation and voice beliefs was also assessed. Method: We identified 56 participants meeting the diagnostic criteria for PTSD with dissociation, SCZ or both diagnoses (PTSD + SCZ) who also experienced auditory hallucinations. Measures included PTSD Symptoms Scales Interview (PSSI-5), Psychotic Symptoms Rating Scale (PSYRAT), Clinician Administered Dissociative States Scale (CADSS), Beliefs about Voices Questionnaire (BAVQ) and Positive and Negative Syndrome Scale (PANSS). Results: Beliefs about voices were similar across diagnostic groups. Participants with SCZ were more likely to attribute their voices to an external origin, and participants with dual diagnosis were less able to control their voices. The PTSD-only group scored higher in dissociation scores than either the SCZ-only or dual diagnosis group. Malevolent voice appraisals correlated with dissociation scores only in the dual diagnosis group. Conclusions: This research supports the hypothesis that voice beliefs are similar across diagnoses of PTSD and SCZ. However, differences in voice characteristics, emotional responses and relationship to dissociation may need to be considered in the psychological management of voices.